Coxsackievirus A6 and Hand, Foot, and Mouth Disease, Finland - Riikka Österback; Tytti Vuorinen; Mervi Linna; Petri Susi; Timo Hyypiä; Matti Waris (Emerging Infectious Diseases, 2009)
During fall 2008, an outbreak of hand, foot, and mouth disease (HFMD) with onychomadesis (nail shedding) as a common feature occurred in Finland. We identified an unusual enterovirus type, coxsackievirus A6 (CVA6), as the causative agent. CVA6 infections may be emerging as a new and major cause of epidemic HFMD.